Social Evolution and Sociological Categories. - Hirst, Paul (Routledge revivals., 2009)
First published in 1976, this book is concerned with the nature of classification in the social sciences. Its thesis is that classifications are dependent upon and are derived from theoretical explanations. Classification is not a theoretically neutral typification or ordering of social forms. This is because objects classified societies, social institutions are not given to knowledge independently of the categories which construct them and because the categories of classification are themselves the products of theories.